Da Memória à Construção de Narrativas Presentes: a Experiência do Centro de Memórias do Museu do Trabalho Michel Giacometti. 9 anos. Comecei a Trabalhar na Fábrica aos 9 anos (Tia Ana, 2008, Setúbal) - Cardoso, Maria Miguel (Trabalhos de Antropologia e Etnologia, 2020)
The Centre of Memories from the Museum of Labour Michel Giacometti is a project that aims to gather collective, and individual memories. In the museum context, this participative action contributes to increase, and democratize, the nature of knowledge. Intimately connected with the museum’s collections of different objects and photographs, the communication of these memories brought us back to heritage’s focus: the relationship between man and objects. In 2017 the museum renewed its museography, and these memories were a strong influence and source for the process. Double standard narratives were adopted, the beauty and the ‘beast’ were exhibited – placing the museum between theory, and life.